2022
DOI: 10.1186/s12872-022-02526-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between total ischemic time and in-hospital mortality after emergency PCI in patients with acute ST-segment elevation myocardial infarction: a retrospective study

Abstract: Background Symptom-to-balloon time (SBT) represents the total ischemic time in ST-elevated myocardial infarction (STEMI) and is associated with poor long-term outcomes. The study aimed to explore the association between SBT and in-hospital mortality after emergency percutaneous coronary intervention (PCI) in patients with acute STEMI. Methods This retrospective, multicenter, observational study included patients admitted to the Hebei General Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…One patient was expired due to high TIMI score. An international study conducted by Gao 21 reported almost same results 21 .…”
Section: Discussionmentioning
confidence: 53%
“…One patient was expired due to high TIMI score. An international study conducted by Gao 21 reported almost same results 21 .…”
Section: Discussionmentioning
confidence: 53%
“…Numerous studies have demonstrated the connection between TIT and the prognosis following PCI in patients with STEMI [16,22]. This study's key conclusion was the identification of a direct link between TIT and various in-hospital complications, such as pulmonary edema and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 79%
“…It may be a more powerful prognostic indicator than DTB time, as an increase in microvascular blockage area has been linked to extended ischemia [15]. Gao and co-authors found that in patients with STEMI with ejection fraction (EF) < 50%, TIT was independently correlated with all-cause mortality in the hospital after PCI [16]. The findings of this study also reveal that acute kidney injury, Killip, and thrombolysis in myocardial infarction (TIMI) grade are substantial risk factors for in-hospital death in STEMI patients [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the invention of coronary artery stents, stenting has been regarded as the major post-procedural complication of percutaneous coronary intervention stent thrombosis. 1,2 The development of drug-eluting stents (DES) was specically one of the important developments in interventional cardiology. 3,4 With an initial higher risk of acute stent thrombosis, drug-eluting stents have been demonstrated to minimize in-stent restenosis and eventual target lesion revascularization.…”
Section: Introductionmentioning
confidence: 99%